Dasotraline as a selective cytochrome 2B6 inhibitor for reaction phenotyping. (9th December 2019) - Yang, Xin; Ryu, Sangwoo; Di, Li
Abstract: Reaction phenotyping using human liver microsomes or hepatocytes with chemical inhibitors is one of the most commonly applied methods to assess the fraction metabolized (fm ) of drug candidates by enzymes. The fm information is critical to understanding the risk of victim drug–drug interactions in the clinic. Inhibitor selectivity is essential in order to generate reliable data and irreversible inhibitors are often preferred over reversible inhibitors to minimize the impact of inhibitor depletion. Although many selective cytochrome P450 (CYP) inhibitors are available, the identification of selective CYP2B6 inhibitors has been challenging due to cross inhibition to the other enzymes. In this study, dasotraline was evaluated as a selective inactivator of CYP2B6 under reaction phenotyping conditions with human hepatocytes. The results show that dasotraline is a very selective inactivator for CYP2B6 with minimal inhibition to other enzymes. A concentration of 0.1 μM dasotraline is recommended for reaction phenotyping with a hepatocyte cell density of 0.5 million cells/ml or 0.5 μM for 2 million cells/ml, when using a 15 minute preincubation, as well as the protocol of inactivator removal before the addition of substrates.